The travails of setting up a living donor liver transplant program: Experience from Pakistan and lessons learned. Issue 7 (July 2015) - Dar, Faisal Saud; Bhatti, Abu Bakar Hafeez; Dogar, Abdul‐Wahab; Zia, Haseeb; Amin, Sadaf; Rana, Atif; Nazer, Rashid; Khan, Nasir Ayub; Khan, Etizaz‐ud‐din; Rajput, Muhammad Zameer; Salih, Muhammad; Shah, Najmul Hassan
<x xml:space="preserve">Abstract</x> Living donor liver transplantation (LDLT) is the only treatment option for patients with end‐stage liver disease (ESLD) where cadaveric donors are not available. In developing countries, the inception of LDLT programs remains a challenge. The first successful liver transplantation program in Pakistan started transplantation in 2012. The objective of this study was to report outcomes of 100 LDLT recipients in a developing country and to highlight the challenges encountered by a new LDLT program in a resource‐limited setting. We retrospectively reviewed recipients who underwent LDLT between April 2012 and August 2014. Demographics, etiology, graft characteristics, and operative variables were assessed. Outcome was assessed on the basis of morbidity and mortality. All complications of ≥ 3 on the Clavien‐Dindo grading system were included as morbidity. Estimated 1‐year survival was calculated using Kaplan‐Meier curves, and a Log‐rank test was used to determine the significance. Outcomes between the first 50 LDLTs (group 1) and latter 50 LDLTs (group 2) were also compared. Median age was 46.5 (0.5‐72) years, whereas the median MELD score was 15.5 (7‐37). The male to female ratio was 4:1. ESLD secondary to hepatitis C virus was the most common indication (73% patients). There were 52 (52%) significant (≥ grade 3) complications. The most common morbidities were bile leaks in 9 (9%) and biliary strictures in 14 (14%) patients. Overall mortality in patients who underwent LDLT for ESLD was 10.6%. Estimated 1‐year survival was 87%. Patients who underwent transplantation in the latter period had a significantly lower overall complication rate (36% versus 68%; P = 0.01). Comparable outcomes can be achieved in a new LDLT program in a developing country. Outcomes improve as experience increases. Liver Transpl 21:982‐990, 2015. © 2015 AASLD.